Relations between losses in piezoelectric ceramic and the magnitude of its vibration level - M. SZALEWSKI (Archives of Acoustics)
In the paper the method of the mechanical and electrical loss measurements using a piezoelectric transformer has been applied to determine the relations between the losses and the magnitude of the vibration velocity, strain and stress. The measurements and calculations have been realized for the soft and hard PZT-type ceramics. Good accordance of the obtained results with the results obtained by the other authors, applying different measurement methods, proves the usability of the method of loss measurements proposed by the author.